A case of Capgras syndrome with one's own reflected image in a mirror. Issue 2 (3rd March 2016) - Diard-Detoeuf, Capucine; Desmidt, Thomas; Mondon, Karl; Graux, Jérôme
Abstract: We report the case of a 78-year-old patient admitted to the hospital for behavioral and psychological disorders consisting in impressions of presence of a stranger located behind the bathroom mirror, who strikingly shared the patient's appearance but was considered a different person, yet. We discuss how this case can be interpreted as an atypical Capgras syndrome for his mirror image and how it suggests an adjustment of the classical dual-route model that sustains face recognition between covert (or affective) and overt neural pathways.